The Geography of Nowhere : the rise and decline of America's man-made landscape - Kunstler, James Howard (New York ; London : Simon & Schuster, 1993)
Eighty percent of everything ever built in America has been built since the end of World War II. This tragic landscape of highway strips, parking lots, housing tracts, mega-malls, junked cities, and ravaged countryside is not simply an expression of our economic predicament, but in large part a cause. It is the everyday environment where most Americans live and work, and it represents a gathering calamity whose effects we have hardly begun to measure." "In The Geography of Nowhere, James Howard Kunstler traces America's evolution from a nation of Main Streets and coherent communities to a land where everyplace is like noplace in particular, where the city is a dead zone and the countryside a wasteland of cars and blacktop. Now that the great suburban build-out is over, Kunstler argues, we are stuck with the consequences: a national living arrangement that destroys civic life while imposing enormous social costs and economic burdens. Kunstler explains how our present zoning laws impoverish the life of our communities, and how all our efforts to make automobiles happy have resulted in making human beings miserable. He shows how common building regulations have led to a crisis in affordable housing, and why street crime is directly related to our traditional disregard for the public realm." "Kunstler takes the reader on a historical journey to understand how Americans came to view their landscape as a commodity for exploitation rather than a social resource. He explains why our towns and cities came to be wounded by the abstract dogmas of Modernism, and reveals the paradox of a people who yearn for places worthy of their affection, yet bend their efforts in an economic enterprise of destruction that degrades and defaces what they most deeply desire." "Kunstler proposes sensible remedies for this American crisis of landscape and townscape: a return to sound principles of planning and the lost art of good place-making, an end to the tyranny of compulsive commuting, the unreality of the suburb, the alienation and violence of downtown, the vulgarity of the highway strip, and the destruction of our countryside. The Geography of Nowhere puts the issue of how we actually live squarely at the center of our ongoing debate about the nation's economy and America's future
Scary places -- American space -- Life on the gridiron -- Eden updated -- Yesterday's tomorrow -- Joyride -- The evil empire -- How to mess up a town -- A place called home -- The loss of community -- Three cities -- Capitals of unreality -- Better places
"A Touchstone book."
Includes bibliographical references and index.
Keywords: Architecture -- Environmental aspects -- United States; Architecture and society -- United States